Alcott in her own time : a biographical chronicle of her life, drawn from recollections, interviews, and memoirs by family, friends, and associates - Shealy, Daniel (Writers in their own time (University of Iowa Press), 2005)
By 1888, twenty years after the publication of Little Women, Louisa May Alcott (1832-1888) was one of the most popular and successful authors America had yet produced. In her pre-Little Women days, she concocted blood-and-thunder tales for low wages; post-Little Women, she specialized in domestic novels and short stories for children. Collected here for the first time are the reminiscences of people who knew her, the majority of which have not been published since their original appearance in the 19th and early 20th centuries. Many of the printed recollections in this book appeared after Alcott.